Psikoedukasi “Strong Family, Smart Kids” Upaya Peningkatan Pengetahuan Serta Identifikasi Perkembangan Kognitif Anak Usia Dini - Wahyu Putri; Djudiyah; ⁠Siti Fasikhah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
Parents' understanding of child development knowledge will be very helpful in parenting. This study aims to develop knowledge and identify children's cognitive development for parents of Kindergarten X Malang City because many parents still do not understand the importance of early stimulation and their role as the main companion in their child's growth and development. The method in this study used a pre-experimental model with a one-group pretest–posttest design, and applied a child's cognitive development measurement scale and the "Playtime Parent's and Teacher's Guide". The results of the t-test analysis obtained t = -7.839) (sig. 000 (p < 0.05). This means there is a difference in parents' knowledge about children's cognitive development before and after being given psychoeducation. The post-test mean (M = 18.00) is greater than the pre-test mean (M = 14.28). The results of the study indicate that the psychoeducation program is significantly able to increase parents' knowledge of cognitive development.